Formation of Porous Apatite Layer during In Vitro Study of Hydroxyapatite-AW Based Glass Composites - Pat Sooksaen; Natyada Pengsuwan; Sittipong Karawatthanaworrakul; Surasak Pianpraditkul (Advances in Condensed Matter Physics)
This research discussed the fabrication, characterization, and in vitro study of composites based on the mixture of hydroxyapatite powder and apatite-wollastonite (AW) based glass. AW based glass was prepared from the SiO2-CaO-MgO-P2O5-CaF2 glass system. This study focuses on the effect of composition and sintering temperature that influences the properties of these composites. Microstructural study revealed the formation of apatite layer on the composite surfaces when immersed in simulated body fluid (SBF) solution at 37°C. Composites containing ≥50 wt% AW based glass showed good bioactivity after 7 days of immersion in the SBF. A porous calcium phosphate (potentially hydroxycarbonate apatite, HCA) layer formed at the SBF-composite interface and the layer became denser at longer soaking period, for periods ranging from 7 to 28 days. Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) analysis showed that early stage of soaking occurred with the release of Ca and Si ions from the composites and the decrease of P ions with slow exchange rate.